Actively preparing for pregnancy is associated with healthier lifestyle of women during the preconception period. (July 2017) - Poels, Marjolein; van Stel, Henk F.; Franx, Arie; Koster, Maria P.H.
Abstract: Objective: To assess whether actively preparing for pregnancy by women is associated with lifestyle changes during the preconception period. Design: retrospective cross-sectional study. Setting: primary care community midwifery practice in the Netherlands. Participants: convenience sample of 283 women who received antenatal care. Measurements and findings: the association between pregnancy preparation (defined as searching for information and/or consulting a healthcare provider) and preconception lifestyle changes (healthier diet, folic acid, alcohol and tobacco cessation) was measured and adjusted for age, body mass index and educational level. Almost 60% ( n =160) of women acquired preconception information themselves and 25% ( n =68) consulted a healthcare provider regarding their pregnancy wish. The former group was significantly more likely to quit drinking (adjusted OR 5.46 (95% CI 1.76–16.96)), improve their diet (adjusted OR 7.84 (95% CI 3.03–20.30)) and use folic acid (adjusted OR 3.90 (95% CI 2.00–7.62)) compared with women who did not prepare for pregnancy. Effect sizes were even larger for women who (also) consulted a healthcare provider with regard to folic acid use, healthier diet and smoking cessation. Key conclusions: gathering preconception information, either by women themselves or by means of a PCC consult, is associated with women positively changing lifestyles during the preconception period. Implications for practice: we recommend to not solely focus interventions on increasing the uptake of PCC consults, yet providing a suitable offer of preconception health information, which enables women to properly inform themselves. Highlights: Two-thirds of women seek preconception health information to prepare for pregnancy. Information seeking is related to positive changes in preconception lifestyle. PCC consultation increases the likelihood of preconception smoking cessation.